2021
DOI: 10.3390/healthcare9020106
|View full text |Cite
|
Sign up to set email alerts
|

Homebound versus Bedridden Status among Those with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: Persons living with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) vary widely in terms of the severity of their illness. It is estimated that of those living with ME/CFS in the United States, about 385,000 are homebound. There is a need to know more about different degrees of being homebound within this severely affected group. The current study examined an international sample of 2138 study participants with ME/CFS, of whom 549 were severely affected (operationalized as ‘Homebound’). A subsample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Other suffering results from long periods of isolation, alienation and loneliness [80]. Conroy, Bhatia, Islam and Jason (2021) found that "next day soreness or fatigue after non-strenuous, everyday activity" and "physically drained or sick after mild activity" were the strongest predictors of reducing victims to 'homebound' status [81].…”
Section: The Nature Of Mus Me and Cfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other suffering results from long periods of isolation, alienation and loneliness [80]. Conroy, Bhatia, Islam and Jason (2021) found that "next day soreness or fatigue after non-strenuous, everyday activity" and "physically drained or sick after mild activity" were the strongest predictors of reducing victims to 'homebound' status [81].…”
Section: The Nature Of Mus Me and Cfsmentioning
confidence: 99%
“…Scientese discourse is used by PS investigators have created a scientific-sounding narrative without substantive empirical support, appropriating scientific credibility without legitimacy. To consider one representative example, consider the following Abstract 24 from Michael Sharpe's (1991) paper "Psychiatric Management of Post Viral Fatigue Syndrome" in the British Medical Bulletin that states [81]:…”
Section: )mentioning
confidence: 99%
“…Recent research studies provide evidence that this classification system is valid and useful [20,21]. Compared to the non-homebound ME/CFS population, homebound patients report more severe and frequent symptoms and greater functional impairment [6].…”
Section: Very Severementioning
confidence: 99%
“…The condition disproportionately affects more women than men [ 1 ] and often follows an episode of viral or bacterial infection [ 2 ]. Once diagnosed, an estimated quarter of patients become bedbound or housebound, and many are unable to work, attend school, or perform daily tasks after 1–2 years [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%